KUALITAS PELAYANAN DAPAT MENINGKATKAN KEPUASAN PASIEN DI KLINIK GIGI GENTAN SURAKARTA - Nasiatul Aisyah Salim; Patria Asda; Nurlisa Meirina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2023)
Oral disease is considered a major health problem because of its high incidence and prevalence worldwide. Dental complaints felt by patients can cause anxiety and stress, so dentists need to provide good dental care services. Paying attention to the quality of service at the dental clinic is the first and most important factor in improving service. Patient satisfaction is one of the key indicators of quality in healthcare organizations. Gentan Dental Clinic Surakarta was founded in 2012. This clinic has not conducted a survey on patient satisfaction levels. This study aims to determine the relationship between service quality and patient satisfaction at the research is quantitative research with a cross sectional approach. The number of samples is 85 people. The sampling technique used purposive sampling with the criteria of patients aged more than 17 years and visiting or receiving services more than once. The research instrument used a questionnaire. Data analysis used the chi square test. The results of the study explained that the quality of service in the good category was 78,8 % and patient satisfaction in the satisfied category was 67,1 %. The statistical test between service quality and patient satisfaction at the Gentan Dental Clinic with a p-value of 0,000.